Implementasi Aplikasi Canva Sebagai Media Pembelajaran PJOK di SDN Sumberharjo Pacitan - Mirza Ariyani; Dedi Dwi Cahyono (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to describe the implementation of the Canva application as a learning medium for Physical Education, Sports, and Health (PJOK) at SDN Sumberharjo Pacitan, and to identify the supporting and inhibiting factors in its application. The method used is qualitative with a descriptive approach, where data were collected through in-depth interviews, direct observation, and documentation techniques. The research subjects include the PJOK teacher and 4th-grade students at SDN Sumberharjo Pacitan. The results indicate that the implementation of Canva is carried out by utilizing premium features through the belajar.id account to create various visual media such as health posters, sports technique presentation slides, and interactive infographics. The use of this media is proven to increase students' enthusiasm, focus, and conceptual understanding in the cognitive, affective, and psychomotor domains. The main supporting factors include principal support, the availability of IT facilities (WiFi, LCD, Smart TV), and the ease of Canva's design features, while the identified inhibiting factor is the instability of the internet network at the school.